Prevalence and determinants of anemia due to micronutrient deficiencies among children aged 12-59 months in India-Evidence from Comprehensive National Nutrition Survey, 2016-18. - Kapil Yadav; Gomathi Ramaswamy; Surabhi Puri; Kashish Vohra; Thejas Achary; Abhishek Jaiswal; Ravneet Kaur; Mohan Bairwa; Archana Singh; Vani Sethi (Public Library of Science (PLoS), 2024)
The present study aimed to estimate the prevalence of anemia, and anemia with micronutrient deficiencies (iron/ vitamin B12/ folic acid) and their determinants among children aged 12-59 months in India. Comprehensive National Nutritional Survey (2016-2018) is Asia's largest nutrition survey conducted among 0-19 years aged children in India. We used generalised linear model (modified Poisson) with adjusted prevalence ratio (aPR) to assess the socio-economic and biochemical factors associated with anemia and anemia with micronutrient deficiencies amongst children aged 12 to 59 months. Out of the total of 11,237 children included in the study, 40.5% (95%CI:38·6-42·6) were anemic, 30.0% (95%CI:27·8-32·4) had anemia with micronutrient deficiencies and 60.9% (95%CI:58·2-63·5) had micronutrient deficiencies with or without anemia. Younger age (aPR(95%CI) for one year old: 1.9(1.5-2.4), two year old: 1.8(1.5-2.2), three year old: 1.4(1.2-1.7) compared to four year old children) and lower educational status of the mother (mothers without formal schooling aPR(95%CI):1.4(1.1-1.8); 1-9 standards: 1.4(1.2-1.7)) vs mother educated with high school and above, consumption of less than 100 iron-folic acid tablets during pregnancy (aPR(95%CI):1.3(1.0-1.7) vs consumption of ≥ 180 tablets, any self-reported illness among children within two weeks preceding the interview (aPR(95%CI):1.2(1.1-1.4) vs no-illnesses, iron deficiency (aPR(95%CI):2.2(2.0-2.6)) and zinc deficiency (aPR(95%CI):1.3(1.1-1.4)) were associated with anemia in children. Among anemic, the children from scheduled tribe (aPR(95%CI):1.4(1.1-1.8)) vs other caste categories, and those following unsafe child faeces disposal practices (aPR(95%CI):1.2(1.0-1.4)) vs those who follow safe faeces disposal practices had higher chance of having micronutrient deficiency. One third of children aged 12-59 months had anemia with micronutrient deficiency (iron/ folic acid/ vitamin B12). More than half of children had micronutrient deficiencies irrespective of anemia. Micronutrient deficiencies, antenatal IFA intake, safe hygiene practices need to be strengthened to leave no stone unturned in control of anemia among under-five children in India.